Subclavian Artery to Internal Carotid Artery Interpositional Bypass for Carotid Artery Occlusion: Technical Case Report. Issue 1 (7th September 2020) - Catapano, Joshua S; Frisoli, Fabio A; Paisan, Gabriella M; Dunn, Katherine A; Bajaj, Ankush; Labib, Mohamed A; Cole, Tyler S; Lang, Michael J; Lawton, Michael T
Abstract: BACKGROUND AND IMPORTANCE: Conventional microsurgical treatment for symptomatic internal carotid artery (ICA) occlusion is revascularization with superficial temporal artery (STA) to middle cerebral artery bypass. However, in rare cases where the common carotid artery, external carotid artery (ECA), or both are also occluded, other microsurgical treatment options must be considered. CLINICAL PRESENTATION: We present the case of a 52-yr-old woman with common carotid artery occlusion and weak ICA flow from collateral connections between the vertebral artery, occipital artery, and ECA. She had ischemic symptoms and a history of stroke. The patient's STA was unsuitable as a donor vessel due to its small caliber and poor flow, and we instead performed an interpositional bypass from the subclavian artery to the ICA using a radial artery graft. CONCLUSION: This case illustrates the successful use of the subclavian artery to ICA bypass technique with an interpositional radial artery graft. The surgical anatomy of the subclavian arteries is reviewed, and the technical details of subclavian artery to radial artery graft to ICA interpositional bypass are presented.